Speculative Markets Drug Circuits and Derivative Life in Nigeria - Peterson, Kristin (Experimental futures : technological lives, scientific arts, anthropological voices, 2014)
In this unprecedented account of the dynamics of Nigeria's pharmaceutical markets, Kristin Peterson connects multinational drug company policies, oil concerns, Nigerian political and economic transitions, the circulation of pharmaceuticals in the Global South, Wall Street machinations, and the needs and aspirations of individual Nigerians. Studying the pharmaceutical market in Lagos, Nigeria, she places local market social norms and credit and pricing practices in the broader context of regional, transnational, and global financial capital. Peterson explains how a significant and formerly profitable African pharmaceutical market collapsed in the face of U.S. monetary policies and neoliberal economic reforms, and she illuminates the relation between that collapse and the American turn to speculative capital during the 1980s. In the process, she reveals the mutual constitution of financial speculation in the drug industry and the structural adjustment plans that the IMF imposed on African nations. Her book is a sobering ethnographic analysis of the effects of speculation and "development" as they reverberate across markets and continents, and play out in everyday interpersonal transactions of the Lagos pharmaceutical market